1987
DOI: 10.1038/bjc.1987.244
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and metastatic murine melanoma variants: motility, adhesiveness, cell surface and in vivo properties

Abstract: The results show enhanced differences in metastatic potential of tight and loose clones after selective cloning and that there may be important differences in motility and cell-substrate interactions. Foulds (1949) introduced the term tumour progression to describe the process by which some tumours become more malignant during their growth. Nowell (1976) attributed this to genetic instability, although genetic or epigenetic processes could result in the emergence of variant cells with growth advantages which d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
(42 reference statements)
1
2
0
Order By: Relevance
“…Our finding, that 74AD cells showed less lung-colonizing ability than 74FL cells, is fundamentally consistent with some studies [7,8,[16][17][18][19][20][21] and inconsistent with others, showing positive correlation [22][23][24] or no distinct difference [25,26] in the adhesive abilities of high and low metastatic cells to culture substrates. Conflicting results are not particularly surprising, because assays are considered only a means to search for the element(s) associated with the properties and metastatic potential of tumor cells in specific experiments.…”
Section: Discussionsupporting
confidence: 65%
“…Our finding, that 74AD cells showed less lung-colonizing ability than 74FL cells, is fundamentally consistent with some studies [7,8,[16][17][18][19][20][21] and inconsistent with others, showing positive correlation [22][23][24] or no distinct difference [25,26] in the adhesive abilities of high and low metastatic cells to culture substrates. Conflicting results are not particularly surprising, because assays are considered only a means to search for the element(s) associated with the properties and metastatic potential of tumor cells in specific experiments.…”
Section: Discussionsupporting
confidence: 65%
“…A transition from a flat to a spherical shape has also been described for the human intestinal Caco‐2 cell line (Basson et al, 1996) and for the human pancreatic adenocarcinoma PaTu 8902 cell line (Paddenberg et al, 1998) after selection on extracellular matrix components. In a number of models, a roundish morphology has been related to a reduced adhesion to solid substrates and a more aggressive phenotype in cancer (Raz and Ben‐Ze'ev, 1983; Clark et al, 1987). The smaller size of T84SF cells might have been selected for cells displaying less mechanical resistance during transendothelial migration and penetration in the target tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore the TNF-susceptible cells form large, loosely packed ('loose') colonies whereas their TNF-resistant sublines form smaller, more tightly packed ('tight') colonies (Matthews & Neale, 1989). Similar colonial variants of tumour cell lines have been described previously and are of more than theoretical interest as 'loose' colony variants of murine melanoma cells have greater metastatic potential than the 'tight' variants (Clark & Sidebottom, 1984;Clark et al, 1987). Similarly, we have found that 'loose' U937A cells are more invasive and metastatic in vivo than 'tight' U937A/R cells (Neale et al, 1990).…”
mentioning
confidence: 82%